Lithuanian Education: Effective, Efficient, High Quality and Equitable? - Želvys, Rimantas; Dukynaitė, Rita; Stumbrienė, Dovilė; Jakaitienė, Audronė (Acta Paedagogica Vilnensia, 2021)
This paper discusses the problem of educational quality. The definition of quality is very broad; therefore, it is more convenient to use the term “educational effectiveness”. Effectiveness can be measured by choosing quantitative indicators that should reflect the level of student achievement as well as equity. It is also important to measure educational efficiency – the output in relation to the input. The current review presents key findings of research conducted in the domain of educational effectiveness and efficiency. The main conclusion of the research paper is that the currently existing mythology of educational quality should be replaced by evidence-based education policy.
Keywords: educational quality; effectiveness; efficiency; equity